Integrating technology into young learners' classes: language teachers' perceptions. Issue 8 (1st November 2020) - Taghizadeh, Mahboubeh; Hasani Yourdshahi, Zahra
Abstract: To ensure the successful implementation of technology in young learners' classroom, the significant role of teachers in the appropriate use of related technologies should be considered. The purpose of this study was thus to examine the attitude, knowledge, use, and challenges of English teachers of young learners to integrate technological tools into language classes. Survey data were collected from 95 young learner English language teachers working in language institutes and schools in Iran. The survey was comprised of four parts, namely technological tools questionnaire, teachers' attitude questionnaire, teachers' challenges questionnaire, and 11 open-ended questions. The results of the study revealed that there was a general positive tendency towards the integration of technology into young learner classes. The results also showed that most teachers did not have sufficient pedagogical and technological knowledge to use technology to teach the English language to young learners. The findings also revealed that a large number of teachers were not provided with training courses on the use of technology in young learners' classes; however, they were willing to participate in technology-based professional development programs. Limited computer facilities, teachers' lack of skills, and lack of support from schools and institutes were found to be the major challenges of using technology in young learners' classes. The findings of this study encourage other researchers to carry out more in-depth studies on the implementation of technological tools in language classes of young learners.